Moral Panics and the Copyright Wars (Journal of Open Law, Technology & Society, 2010)
Copyright holds a fascination for members of the free and open source community. The copyleft nature of the GPL can exist only because copyright laws exist. This review considers William Patry's book “Moral Panics and the Copyright Wars”, and examines its argument that copyright laws are not fit for purpose.